Analisa Daya Dukung Tanah pada Perencanaan Landfill PLTU Suge Belitung - Yayu Hamzah; Satria Agung Wibawa; Yunus Renggana (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The need for landfill facilities as a place for storing B3 waste in several PLTUs and industries is increasingly becoming a priority. This is because the solid waste piles are generated in large quantities. The problem faced is how to get a construction site with landfill facilities in an area that meets the technical requirements in a timely and safe manner. In planning the PLTU Suge - Belitung landfill facility, the quality of the carrying capacity of the local land must be considered in order to determine a Liner layer construction plan (landfill base layer) and a strong and safe Embankment construction plan. The purpose of this research is to get the results of land carrying capacity quality which can then be used for the design of landfill embankment plans. To measure the carrying capacity of the soil in the field using the Standard Penetration Test / SPT. From the calculation of the carrying capacity based on the SPT data, the result is that the carrying capacity (q b) is between 24.06 – 60.29 tons/m2 (average = 36.51 tons/m2), while the permit carrying capacity (q a) is between 8.02 – 20.10 tonnes/m2 (average = 12.17 tonnes/m2).